Forage Resources of Telangana State and Research Technology for Enhancing Fodder Production - Shashikala, T.; Susheela, R.; Naaiik, R. Balazzii; Shanti, M.; Devi, K. B. Sunitha; Chandrika, V.; Murali, B. (International Journal of Economic Plants, 2017)
Livestock are an important asset and livelihood option for poor people in rain fed areas, but poor feed quality and dry season feed shortages are a serious limitation for sustainable livestock production. The cattle and buffaloes are normally fed on the fodder available from cultivated crops, supplemented to a small extent by harvested grasses and top feeds (tree leaves). While small ruminants usually depend on grazing and top feeds, either browsed or lopped from shrubs and trees. Better feeding could be achieved by ensuring the adequate supply of good quality forage from better varieties and improved cultural practices. Fodder production and its utilization depend on the cropping pattern, climate, socio-economic conditions and type of livestock. Keeping this in view the Forage Research scheme i.e. AICRP on Forage Crops, PJTSAU, Hyderabad has been formulated the mandate areas of research such as development of improved cultivars and contributed technologies for improving fodder production of various cultivated fodder crops. Since its inception six varieties were developed and released for cultivation in state of Telangana and Andhra Pradesh. The Bajra Napier hybrid APBN-1 released from the centre is very popular even in the state of Gujarat with commendable area under cultivation. Many fodder production technologies were developed and were adopted by farming community.